Impact of Human Capital on Pro-Poor Growth in Cameroon - Alexis, Tiomela Yemedjeu; Christophe, Kuipou Toukam; Herve, Sonwa Dongue Ghislain (International Journal of Publication and Social Studies, 2020)
The objective of this study is to determine the impact of human capital on pro-poor growth in Cameroon. To achieve this goal, we used multiple correspondence analysis to build the composite indicator of education and health. To analyze the impact of human capital on pro-poor growth, we used the relative approach of Kakwani, Neri, and Son (2010). The data used for this study come from the third and fourth Cameroonian household surveys. The results show that there was a loss of growth in education and health between 2007 and 2014, the level of education of the poor improved less while their level of health deteriorated more by compared to the middle layer. The loss of growth in human capital has had a negative impact on the level of well-being of populations. Taking into account these results, the supply and quality of educational and health infrastructures in urban and rural areas but especially in rural area, the promotion and diversification of professional and technical training, the reduction in the cost of consultations and medicines, the increase of education and health personnel are our main recommendations.